Modified graphite material, preparation method and application thereof, and battery

By covering the composite coating agent of alumina and liquid asphalt on the surface of the graphite material, the modified graphite material is formed, which solves the problem of poor thermal stability and first-term effect of existing graphite materials in lithium-ion batteries, and achieves the excellent performance of modified graphite materials in lithium-ion batteries.

CN119786562AActive Publication Date: 2025-04-08SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411972190.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing graphite materials have problems of poor thermal stability and poor first-term efficiency in lithium-ion batteries, especially during high-rate charging and discharging and circulation, which are prone to electrolyte penetration, structural expansion and capacity decline.

Method used

A composite graphite material is used, which consists of graphite material and a cladding layer containing alumina and carbon. The modified graphite material is formed by coating a composite coating agent of alumina and liquid asphalt on the surface of the graphite material. The method includes mixing aluminum salt, liquid asphalt and solvent to form a composite coating agent, and mixing it uniformly with the graphite material, followed by heat treatment and carbonization to obtain a modified graphite material.

Benefits of technology

Modified graphite materials show excellent first-effect and cycling performance in lithium-ion batteries, significantly improved discharge capacity, rate performance and kinetic performance, and have good thermal stability under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786562A_ABST
    Figure CN119786562A_ABST
Patent Text Reader

Abstract

The invention discloses a modified graphite material, a preparation method and application thereof and a battery. The modified graphite material comprises a graphite material and a coating layer, the coating layer contains aluminum oxide and carbon. The preparation method of the modified graphite material comprises the following steps: S1, stirring a mixture containing aluminum salt, liquid phase pitch and a solvent to obtain a composite coating agent; the mass ratio of the aluminum salt to the liquid phase pitch is (3-7): (5-15); the solubility of the aluminum salt at 25 DEG C is 50 g / 100 mL or more, such as 70 g / 100 mL; s2, uniformly mixing the composite coating agent in the step S1 with a graphite material to obtain the graphite material coated with the composite coating agent; s3, performing heat treatment and carbonization on the graphite material coated with the composite coating agent to obtain a modified graphite material; the temperature of the heat treatment is 350-500 DEG C. The finally obtained modified graphite material has good cycling stability and excellent electrochemical performance, and is suitable for high-performance lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified graphite material and a preparation method, application and battery thereof. Background Art

[0002] In the field of lithium-ion batteries, the performance of negative electrode materials directly affects the overall performance and service life of the battery. Graphite, as a traditional negative electrode material, is widely used due to its excellent conductivity and stable structure. However, graphite materials are prone to problems such as electrolyte penetration, structural expansion and capacity decay during high-rate charge and discharge and cycling, which limits the further development of its application.

[0003] In order to solve these problems, surface coating technology has been proposed as an effective improvement method. By coating a protective film on the surface of graphite materials, its electrochemical performance can be enhanced and its cycle stability can be improved. Among them, nano-aluminum oxide film has become an ideal coating material due to its excellent mechanical strength and chemical stability. Liquid asphalt, as an organic material with good adhesion, can effectively improve the conductivity and interface stability of the negative electrode.

[0004] Patent CN113363445A discloses a method for coating modified graphite materials with mesh γ-alumina. The method first mixes a graphite dispersion solution with an aluminum salt solution in a specific proportion, and then adds an appropriate amount of alkaline substance to adjust the pH value to form a sol slurry. Next, an aging reaction is carried out at 50 to 120°C for 2 to 6 hours, and then the slurry is dried and crushed. Finally, the precursor is calcined at a high temperature in an inert atmosphere, and the modified graphite material can be obtained after crushing and screening. Although this modified graphite material can enhance the mechanical strength and chemical stability of the negative electrode, its conductivity is relatively low, and it is difficult to control the coating uniformity.

[0005] Patent CN115911304A introduces a liquid phase asphalt coated graphite material and its preparation method. The method is to uniformly mix graphite with liquid phase asphalt, then perform high temperature carbonization treatment on the surface coating layer, and finally obtain the liquid phase coated graphite material by screening and demagnetization. The advantage of this method is that the liquid phase coating agent has good fluidity and can achieve uniform coating. Although the negative electrode material has good electrical conductivity and interface contact, and can improve the conductivity of the negative electrode, it may degrade and induce side reactions under high temperature conditions, and has poor thermal stability. Summary of the invention

[0006] In order to solve the defects of poor thermal stability and initial efficiency of lithium ion batteries using graphite materials as negative electrode materials in the prior art, the present invention provides a composite graphite material and its preparation method, application and lithium ion battery. The composite graphite material is used as a negative electrode material in a lithium ion battery, and the obtained lithium ion battery not only has excellent initial efficiency and cycle performance, but also has good discharge capacity, rate performance and kinetic performance.

[0007] The present invention adopts the following technical solutions to solve the above technical problems:

[0008] The invention provides a modified graphite material, which comprises a graphite material and a coating layer; the coating layer contains aluminum oxide and carbon.

[0009] The content of magnetic substance in the modified graphite material may be 0.1-0.6 ppm, for example, 0.347 ppm, 0.481 ppm, 0.545 ppm or 0.532 ppm.

[0010] The D10 of the modified graphite material may be 4-6 μm, for example, 5.31 μm, 5.22 μm, 5.16 μm or 5.07 μm.

[0011] The D50 of the modified graphite material may be 10-12 μm, for example, 11.51 μm, 11.38 μm, 11.21 μm or 11.19 μm.

[0012] The D90 of the modified graphite material may be 31-33 μm, for example, 32.10 μm, 31.46 μm, 31.13 μm or 31.01 μm.

[0013] The specific surface area of ​​the modified graphite material can be 1.5-2.5m 2 / g, for example 2.04m 2 / g, 1.98m 2 / g, 1.89m 2 / g or 1.87m 2 / g.

[0014] The present invention provides a method for preparing a modified graphite material, which comprises the following steps:

[0015] S1. Stirring a mixture containing aluminum salt, liquid asphalt and solvent to obtain a composite coating agent; the mass ratio of the aluminum salt to the liquid asphalt is (3-7):(5-15); the solubility of the aluminum salt at 25° C. is 50 g / 100 mL or more, for example, 70 g / 100 mL;

[0016] S2, mixing the composite coating agent and the graphite material in step S1 uniformly to obtain a graphite material coated with the composite coating agent;

[0017] S3. The graphite material coated with the composite coating agent is subjected to heat treatment and carbonization to obtain a modified graphite material; the heat treatment temperature is 350-500°C.

[0018] In the present invention, the aluminum salt may be anhydrous aluminum nitrate and / or aluminum nitrate nonahydrate, for example, aluminum nitrate nonahydrate.

[0019] In a preferred embodiment, the aluminum salt is aluminum nitrate nonahydrate. Aluminum nitrate nonahydrate is also called aluminum nitrate nonahydrate, and its chemical formula is H 18 AlN3O 18 , which can be expressed by Al(NO3)3·9H2O.

[0020] For easy storage and use, aluminum nitrate nonahydrate should be stored in a cool, dry, well-ventilated warehouse. Keep away from fire and heat sources. The package must be sealed and not exposed to moisture.

[0021] In step S1, the solvent may be a solvent conventionally used in the art. Preferably, the solvent may be deionized water and / or ethanol. More preferably, the solvent may be deionized water and ethanol, and the volume ratio of the deionized water to the ethanol may be (1-10):1, such as 1:1, 1.5:1, 2.33:1 or 4:1.

[0022] In step S1, the mass ratio of the aluminum salt to the solvent may be (0.2-0.8):1, such as 0.6:1, 0.5:1, 0.4:1 or 0.3:1.

[0023] In a specific embodiment, if the solvent is too little, the fluidity of the coating agent is too poor, resulting in uneven coating and affecting material properties; if the solvent is too much, after mixing with graphite, the material humidity is high and agglomeration will occur in the subsequent heat treatment stage.

[0024] In step S1, the mass ratio of the aluminum salt to the liquid asphalt may be 6:10, 5:10, 4:10 or 3:10.

[0025] In step S1, the density of the liquid asphalt can be 0.5-1.5 g / cm 3 , for example 1.10 g / cm 3 .

[0026] In step S1, the sulfur content of the liquid phase asphalt may be less than 0.15 wt%, for example, 0.10 wt%.

[0027] In step S1, the ash content of the liquid phase asphalt may be less than 0.03 wt%, for example, 0.01 wt%.

[0028] The meaning of ash content is: the weight ratio of the residue after dry liquid asphalt is burned to constant weight at 800±20℃ under air conditions to the weight ratio of the original sample.

[0029] In step S1, the coking value of the liquid phase asphalt can be 5-20wt%, such as 5wt%, 10wt%, 15wt% or 20wt%. The coking value means: the percentage of the weight of coke formed after the asphalt undergoes thermal decomposition and polycondensation reaction during heating to the weight of the original coal tar.

[0030] The dilution ratios of different coking values ​​are different. In order to ensure the residual carbon content of asphalt coating, the coking value needs to be determined at a certain dilution ratio. This can ensure both the fluidity of the coating agent and the residual carbon content.

[0031] In step S1, the residual carbon of the composite coating agent may be 0.5wt%-2.0wt%, such as 0.5wt%, 1wt%, 1.5wt% or 2wt%. Wherein, too large residual carbon value will affect the specific surface area of ​​the material and reduce the material performance.

[0032] The residual carbon value means the mass fraction of the charred black residue formed after thermal evaporation, cracking and combustion.

[0033] If the residual carbon value is too high, side reactions are likely to occur, resulting in performance degradation. If the residual carbon value is too low, the fast charging effect is not significantly improved.

[0034] In a specific embodiment, the liquid phase asphalt can be diluted with condensate oil so that the coking value of the liquid phase asphalt is 5-20wt%. The condensate oil is a carbonized product of the production line of Shanshan New Materials Co., Ltd. The main component of the condensate oil is a mixture of C5 to C11+ hydrocarbons, and contains a small amount of hydrocarbons greater than C8 and impurities such as sulfur dioxide, thiophenes, mercaptans, sulfides and polysulfides.

[0035] In step S1, the stirring time may be 10 to 20 minutes, for example, 10 minutes.

[0036] In step S1, the stirring temperature is a temperature conventionally used in the art. Preferably, the stirring temperature is room temperature, which is 15-30°C.

[0037] In step S2, the graphite material is a graphite material commonly used in the art. The graphite material can be artificial graphite and / or natural graphite, for example, artificial graphite.

[0038] In step S2, the mass ratio of the composite coating agent to the graphite material may be (1-3):10, for example, 1.6:10, 1.5:10, 1.4:10 or 1.3:10.

[0039] In the present invention, too little coating agent will not easily form a complete film structure, and too much coating agent will cause agglomeration.

[0040] In step S2, the mass proportion of the liquid asphalt in the composite coating agent can be 5wt% to 15wt% to improve the conductivity and chemical stability of the negative electrode.

[0041] In the present invention, when determining the alumina coating ratio, it should be calculated based on the conversion ratio between aluminum salt and alumina.

[0042] In a preferred embodiment, when determining the alumina coating ratio, it should be calculated by the conversion ratio between aluminum nitrate nonahydrate and alumina, and after dilution, aluminum nitrate nonahydrate will first decompose into aluminum ions (Al 3+ ) and nitrate ions (NO 3- ), and at the same time, water molecules and aluminum ions undergo hydration. Due to the introduction of solutes, the volume of the solution increases due to the dissolution of the solutes. This is because during the dissolution process in water, water molecules are occupied and form a new solution structure.

[0043] In step S2, the mixing is performed by a mixing method conventionally used in the art.

[0044] In a preferred embodiment, the mixing in step S2 is performed in a fusion machine. The mixing speed can be 400-900 rad / min, such as 900 rad / min. The mixing time in step S2 can be 5-15 min, such as 10 min.

[0045] In a preferred embodiment, the heat treatment in step S3 is carried out in a segmented heating manner, which includes the following steps:

[0046] ① Heating to 250-400°C, such as 400°C, 350°C, 300°C or 250°C; the heating rate may be 1-5°C / min, such as 1.5°C / min; the constant temperature time of heating may be 2-5h, such as 4h, 3.5h, 3h or 2.5h;

[0047] ② Continue heating to 400-600°C, such as 600°C, 550°C, 500°C or 450°C; the heating rate may be 1-5°C / min, such as 1.5°C / min; the constant temperature time of heating may be 5-10h, such as 7h, 6.5h, 6h or 5.5h.

[0048] In a preferred embodiment, the composite coating agent in step S3 is generated in situ on the surface of the graphite material, that is, alumina is generated by an in situ reaction at a high temperature on the surface of the particles.

[0049] In a preferred embodiment, an inert gas is introduced during the heat treatment in step S3, wherein the inert gas is one or more of nitrogen, argon and helium, such as argon.

[0050] In a specific implementation scheme, after the heat treatment in step S3, it is necessary to cool to room temperature before the carbonization step.

[0051] In step S3, the carbonization temperature may be 950-1350°C, such as 1300°C, 850°C, 1000°C or 1150°C.

[0052] In step S3, the carbonization time may be 4-10 hours, for example, 5 hours.

[0053] In a preferred embodiment, step S3 further includes a screening step after the carbonization. The particle size range of the screening can be 100-400 mesh, such as 300 mesh.

[0054] The present invention provides a modified graphite material, which is prepared by the above-mentioned method for preparing the modified graphite material.

[0055] The present invention provides an application of the modified graphite material as described above as a negative electrode material in a lithium ion battery.

[0056] The present invention also provides a lithium ion battery, which comprises the modified graphite material as described above.

[0057] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0058] The reagents and raw materials used in the present invention are commercially available.

[0059] The positive and progressive effects of the present invention are:

[0060] (1) The present invention adds liquid asphalt while coating alumina. The coating agent has good fluidity and can effectively control the heat generated during the reaction and the uniformity of the reaction, ensuring sufficient contact and reaction between the liquid phase and the solid phase. Compared with coating any one material alone, it not only achieves better structural and performance control technically, but also significantly improves the overall performance of the graphite material in terms of electrochemical performance, conductivity and chemical stability. The obtained modified graphite material has a charge capacity of more than 355.42 mAh / g, an initial efficiency of more than 94.75%, and a capacity retention rate of more than 90.1% for 7 days at high temperature (60°C). The preparation method of the modified graphite material shows the potential for wide application in the field of high-performance lithium-ion batteries.

[0061] (2) The high specific surface area protective layer formed by nano-alumina effectively reduces the direct contact between the electrolyte and graphite, reduces the occurrence of side reactions, and thus prolongs the service life of the electrode. The use of nano-alumina film improves the electrochemical performance of the electrode, improves the conductivity and stability, and can effectively enhance the transmission rate of lithium ions in the electrode material due to its high specific surface area and excellent conductivity.

[0062] (3) Liquid asphalt as a binder enhances the adhesion of the alumina film and avoids peeling during the charge and discharge process. The slow heating during the heat treatment process effectively avoids stress damage to the coating layer, forming a stronger bond between the alumina film and the graphite material, further improving the mechanical strength and electrochemical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 This is an element scanning diagram of the modified graphite material obtained in Example 1. DETAILED DESCRIPTION

[0064] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0065] Liquid asphalt was purchased from Liaoning Xinde New Materials Technology (Group) Co., Ltd.

[0066] Artificial graphite was purchased from Shanshan New Materials Co., Ltd.

[0067] Aluminum nitrate nonahydrate, with a solubility of 70 mg / mL at 25°C, was purchased from Aladdin Biochemical Technology Co., Ltd.

[0068] Aluminum chloride, with a solubility of 45 mg / mL at 25 °C, was purchased from Aladdin Biochemical Technology Co., Ltd.

[0069] Example 1

[0070] S1. Add 500 mL of anhydrous ethanol and 500 mL of deionized water to 600 g of aluminum nitrate nonahydrate for dilution and stir at 25 °C for 10 min. 3 , coking value is 20wt%, sulfur content is 0.10wt%, ash content is 0.01wt%), and stirred evenly at 25°C for 10 minutes to form a composite coating agent (residual carbon value is 2wt%).

[0071] S2, fully fused with 10kg of artificial graphite material (D50 is 10.0±0.5μm) in a fusion machine (speed is 1000rad / min, time is 10min), so that the coating agent is evenly covered to form a graphite material coated with a composite coating agent;

[0072] S3. The graphite material coated with the composite coating agent is heat treated with a hot VC-5 mixer under an argon atmosphere. The heat treatment equipment is operated at 12Hz, the temperature is increased to 400℃ at a heating rate of 1.5℃ / min, the temperature is kept constant for 4h, and then the temperature is continued to be increased to 600℃ at a heating rate of 1.5℃ / min, and the treatment time is 7h; after cooling to room temperature, the coated graphite material is carbonized at 1300℃ (heating rate of 2.5℃ / min) and kept warm for 5h, and then mixed and 300 mesh sieved to obtain a modified graphite material.

[0073] Example 2

[0074] S1. Add 400 mL of anhydrous ethanol and 600 mL of deionized water to 500 g of aluminum nitrate nonahydrate for dilution, and stir for 10 min at room temperature 25 °C. 3 , coking value is 15wt%, sulfur content is 0.10wt%, ash content is 0.01wt%), and stirred evenly at 25°C for 10min to form a composite coating agent (residual carbon value is 1.5wt%).

[0075] S2, fully fused with 10kg of artificial graphite material (D50 is 10.0±0.5μm) in a fusion machine (speed is 950rad / min, time is 10min), so that the coating agent is evenly covered to form a graphite material coated with a composite coating agent;

[0076] S3. The graphite material coated with the composite coating agent is heat treated with a hot VC-5 mixer in an argon atmosphere. The heat treatment equipment is operated at 10Hz, the temperature is increased to 350℃ at a heating rate of 1.5℃ / min, the temperature is kept constant for 3.5h, and then the temperature is continued to be increased to 550℃ at a heating rate of 1.5℃ / min, and the treatment time is 6.5h; after cooling to room temperature, the coated graphite material is subjected to high-temperature carbonization at 1150℃ (heating rate of 2.5℃ / min) and kept warm for 5h, and then mixed and 300-mesh sieved to obtain a modified graphite material.

[0077] Example 3

[0078] S1. Add 300 mL of anhydrous ethanol and 700 mL of deionized water to 400 g of aluminum nitrate nonahydrate for dilution and stir at 25 °C for 10 min. 3 , coking value is 10wt%, sulfur content is 0.10wt%, ash content is 0.01wt%), and stirred evenly at 25°C for 10min to form a composite coating agent (residual carbon value is 1%).

[0079] S2, fully fused with 10kg of artificial graphite material (D50 is 10.0±0.5μm) in a fusion machine (speed is 900rad / min, time is 10min), so that the coating agent is evenly covered to form a graphite material coated with a composite coating agent;

[0080] S3. The graphite material coated with the composite coating agent is heat treated with a hot VC-5 mixer under an argon atmosphere. The heat treatment equipment is operated at 8Hz, the temperature is increased to 300°C at a heating rate of 1.5°C / min, the temperature is kept constant for 3.0h, and then the temperature is continued to be increased to 500°C at a heating rate of 1.5°C / min, and the treatment time is 6h; after cooling to room temperature, the coated graphite material is carbonized at 1000°C (heating rate of 2.5°C / min) and kept warm for 5h, and then mixed and 300 mesh sieved to obtain the final composite coated graphite material.

[0081] Example 4

[0082] S1. Add 200 mL of anhydrous ethanol and 800 mL of deionized water to 300 g of aluminum nitrate nonahydrate for dilution, and stir for 10 min at room temperature 25 °C. 3 , coking value is 5wt%, sulfur content is 0.10wt%, ash content is 0.01wt%), and stirred evenly at 25°C for 10min to form a composite coating agent (residual carbon value is 0.5wt%).

[0083] S2, fully fused with 10kg of artificial graphite material (D50 is 10.0±0.5μm) in a fusion machine (speed of 850rad / min, time of 10min) to make the coating agent evenly cover to form a graphite material coated with a composite coating agent;

[0084] S3. The graphite material coated with the composite coating agent is heat treated with a hot VC-5 mixer under an argon atmosphere. The heat treatment equipment is operated at 6Hz, the temperature is increased to 250°C at a heating rate of 1.5°C / min, the temperature is kept constant for 2.5h, and then the temperature is continued to be increased to 450°C at a heating rate of 1.5°C / min, and the treatment time is 5.5h; after cooling to room temperature, the coated graphite material is subjected to high-temperature carbonization at 850°C (heating rate of 2.5°C / min) and kept warm for 5h, and then mixed and sieved with 300 mesh to obtain a modified graphite material.

[0085] Comparative Example 1

[0086] The comparative example is to coat the nano aluminum oxide film alone in a traditional manner, including the following steps:

[0087] (1) 400 g of aluminum nitrate nonahydrate, 300 mL of anhydrous ethanol and 700 mL of deionized water were mixed and stirred in a stirrer for 10 min at a speed of 300-400 rad / min to form an aluminum oxide precursor solution;

[0088] (2) The alumina precursor solution obtained in step (1) is uniformly stirred to form an alumina coating agent, and is fully fused with the graphite material in a fusion machine so that the coating agent is evenly covered to form a nano alumina film coating layer; the fusion parameters are: 900 rad / min for 10 min;

[0089] (3) The coated graphite material was heat treated in an argon atmosphere using a hot VC-5 mixer. The heat treatment equipment was operated at 8 Hz, and the temperature was raised to 300°C at a heating rate of 1.5°C / min, kept constant for 3.0 hours, and then continued to rise to 500°C for 6 hours; after cooling to room temperature at a cooling rate of 3.0°C / min, the coated graphite material was carbonized at 1000°C and kept warm for 5 hours, with a heating rate of 2.5°C / min, and then mixed and sieved with 300 mesh to obtain the final alumina-coated graphite material.

[0090] Comparative Example 2

[0091] The comparative example is a method of coating liquid asphalt alone in a traditional manner, comprising the following steps:

[0092] (1) The density of 1kg is 1.10g / cm 3 1. Liquid asphalt with a coking value of 10wt% is fully fused with graphite material in a fusion machine to make the coating agent evenly cover and form a liquid asphalt coating layer; the fusion parameters are: 900rad / min for 10min;

[0093] (2) The coated graphite material was subjected to VC heat treatment in an argon atmosphere using a hot VC-5 mixer. The heat treatment equipment was operated at 8 Hz, and the temperature was raised to 300°C at a heating rate of 1.5°C / min, kept constant for 3.0 hours, and then continued to rise to 500°C for a treatment time of 6 hours; after cooling to room temperature at a cooling rate of 3.0°C / min, the coated graphite material was carbonized at 1000°C and kept warm for 5 hours at a heating rate of 2.5°C / min, and then mixed and sieved with 300 mesh to obtain the final liquid phase asphalt coated graphite material.

[0094] Comparative Example 3

[0095] The difference between this comparative example and Example 1 is that aluminum chloride is used instead of aluminum nitrate nonahydrate in step S1.

[0096] Comparative Example 4

[0097] The difference between this comparative example and the embodiment is that the heat treatment step of step S3 is: heating to 100°C at a heating rate of 1.5°C / min, keeping the temperature constant for 4 hours, and then continuing to heat to 200°C at a heating rate of 1.5°C / min, and the treatment time is 7 hours; the remaining steps are the same as Example 1.

[0098] Comparative Example 5

[0099] The difference between this comparative example and Example 1 is that the mass of aluminum nitrate nonahydrate in step S1 is 1 kg and the mass of liquid asphalt in step S2 is 0.5 kg. The remaining steps are the same as Example 1.

[0100] Effect Example 1

[0101] Testing of D10, D50 and D90: Malvern laser particle size tester MS3000 was used to test the particle size range (D10, D50 and D90) and particle size distribution of the material.

[0102] Specific surface area test: The specific surface area of ​​the material was tested using the fully automatic specific surface area and pore size analyzer NOVAtouchTM produced by Quantachrome Instruments of the United States.

[0103] Testing of magnetic substances: The ICP tester Thermo ICAP 7400 is used to test the content of magnetic substances in the material.

[0104] Element scanning: The modified graphite material obtained in Example 1 was scanned using a Thermo Fisher scanning electron microscope Prisma. The results are as follows: Figure 1 shown.

[0105] Direct current internal resistance (DCIR): Use Arbin test cabinet to test material DCIR.

[0106] Effect Example 2

[0107] The LAND battery testing system of Wuhan Landian Electronics Co., Ltd. was used to test the charging and discharging performance of button batteries.

[0108] The modified graphite materials prepared in each embodiment and comparative example were coated on copper foil, vacuum dried at 105°C for 4h, and rolled to prepare negative electrode sheets; a 1mol / L LiPF6 three-component mixed solvent was used as an electrolyte mixed in a volume ratio of ethyl carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1, a polypropylene microporous membrane was used as a diaphragm, and a metal lithium sheet was used as a positive electrode, and button cells were assembled in an inert gas glove box system filled with argon. The button cell charge and discharge test was carried out on the battery test system, at room temperature, 0.1C constant current charge and discharge, and the charge and discharge voltage was limited to 0.005~1.5V.

[0109] (1) First discharge specific capacity and first coulombic efficiency

[0110] Test conditions: the compaction density of the pole piece is 1.65g / cm 3 , the first charge and discharge is performed at a rate of 0.1C, the rate charge and discharge is performed at a current density of 0.1C-2C, and the charging voltage is limited to 0.005-2V. The first coulomb efficiency = (first discharge capacity / first charge capacity)*100%.

[0111] (2) Capacity retention rate

[0112] The compacted density of the pole piece is 1.65g / cm 3 After being stored at 60°C for 7 days, the charge and discharge test was performed at a rate of 0.2C. Capacity retention rate = (charge capacity after high temperature storage / charge capacity before high temperature storage) * 100%.

[0113] The modified graphite materials obtained in Examples 1-4 and Comparative Examples 1-5 were tested using the above test method. The test results are shown in Table 1.

[0114] Table 1

[0115]

[0116] As can be seen from Table 1, the electrochemical performance of the modified graphite materials obtained in Examples 1-4 is better than that of Comparative Examples 1-5. The DCIR of Examples 1-4 is below 4.82Ω, the charge specific capacity is above 355.42mAh / g, the first efficiency is above 94.75%, and the capacity retention rate at 60°C for 7 days is above 90.1%.

[0117] Depend on Figure 1 It can be seen that the inner layer of the prepared modified graphite material is graphite particles, and the outer layer is a coating layer of asphalt and aluminum oxide composite. Aluminum oxide is successfully coated on the surface of graphite particles, indicating that aluminum nitrate nonahydrate reacts in situ to produce aluminum oxide under the action of high-temperature carbonization, and because the fluidity of the coating agent is better, the overall coating effect is more uniform. It can be seen that compared with Comparative Examples 1 and 2 in which any material is coated alone, the present invention not only achieves better structure and performance control in technology, but also significantly improves the overall performance of graphite materials in terms of electrochemical properties, conductivity and chemical stability.

[0118] It can be obtained from Examples 1-4 that the charge gram capacity of the modified graphite material increases with the increase in the amount of aluminum nitrate nonahydrate doped and the increase in the coking value of the liquid phase asphalt. This is because after aluminum nitrate nonahydrate enters the graphite material, aluminum ions will introduce defect sites in the graphite lattice. These defect sites provide more active sites for the adsorption and embedding of lithium ions, allowing lithium ions to interact more easily with the graphite material, thereby increasing the charge gram capacity. A higher coking value helps to increase the degree of graphitization of the graphite material. The increase in the degree of graphitization will make the interlayer spacing of the graphite more regular and the interlayer force stronger, which is conducive to the embedding and extraction of lithium ions between the graphite layers, while also improving the conductivity and structural stability of the material, thereby increasing the charge gram capacity. The particle size, specific surface, etc. of Examples 1-4 and Comparative Examples 1-5 are similar, which shows that the coating amount in different proportions has no significant effect on the morphology and particle size of the negative electrode material.

[0119] The 7-day capacity retention rate at 60°C of Examples 1-4 is significantly better than that of Comparative Examples 1-5. This is because aluminum nitrate nonahydrate decomposes and converts into aluminum oxide (Al2O3) during the heat treatment process. The thermal stability and high temperature resistance of aluminum oxide effectively prevent the oxidation reaction of graphite at high temperatures and enhance its heat resistance.

[0120] Compared to Examples 1-4, the electrochemical performance of Comparative Example 3 is poor, because nitrate itself has strong oxidizability. Under high temperature conditions, nitrate can decompose into oxygen (O2) and nitrogen oxides (such as NO2, NO). These oxidizing substances can produce certain oxidation effects on the graphite surface, expand the interlayer spacing of the graphite material, and thus be beneficial to its electrochemical performance. However, aluminum chloride does not have this effect, and the impurity content of the modified graphite material is high, so its electrochemical performance is poor.

[0121] Compared with Examples 1-4, the electrochemical performance of Comparative Example 4 is poor. This is because the formation of the aluminum oxide layer requires a higher temperature to promote the decomposition of aluminum nitrate, release nitrogen oxides and precipitate to form aluminum oxide. If the heat treatment temperature is too low, aluminum nitrate nonahydrate may not be completely decomposed or converted into aluminum oxide, resulting in an incomplete or uneven aluminum oxide coating, and there will be exposed areas on the graphite surface, affecting the effect of the subsequent carbonization process. Liquid asphalt is generally used to form a protective layer or enhance the bonding between graphite and alumina. Asphalt will pyrolyze during the heat treatment process, releasing volatile components and converting into a stable carbon layer. When the heat treatment temperature is too low, the asphalt may not be fully pyrolyzed, resulting in incomplete carbonization, uneven or insufficient carbon layer formed, which may affect the bonding between graphite and the coating.

[0122] Compared with Examples 1-4, the electrochemical performance of Comparative Example 5 is poor. This is because the content of aluminum nitrate nonahydrate in Comparative Example 5 is high. During subsequent processing or use, due to reactions such as thermal decomposition of aluminum nitrate, large stress may be generated inside the graphite material. When this stress exceeds the tolerance limit of graphite, it is easy to cause cracks or even break the graphite, seriously damaging the overall structural integrity of the graphite, thereby affecting its performance as an electrode material, etc. If the liquid phase asphalt is too little, the coating agent has poor fluidity and uneven coating.

[0123] The above are only some preferred embodiments of the present invention. Any person skilled in the art may modify the technical solutions described above or modify them into equivalent technical solutions. Although the present invention provides specific embodiments, it should be understood that the present invention may be further improved. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes that are out of the scope disclosed in this application and are made with conventional techniques known in the art. Without departing from the concept of the present invention, all other implementation methods that can be thought of by ordinary technicians in this field without creative work, and other simple replacements and various changes to the technical solutions of the present invention, all belong to the protection scope of the present invention.

Claims

1. A modified graphite material, characterized in that: The invention comprises a graphite material and a coating layer; the coating layer contains aluminum oxide and carbon.

2. The modified graphite material according to claim 1, characterized in that: The modified graphite material satisfies one or more of the following conditions ae: a. The content of magnetic substance in the modified graphite material is 0.1-0.6ppm, for example 0.347ppm, 0.481ppm, 0.545ppm or 0.532ppm; b. The D10 of the modified graphite material is 4-6 μm, for example, 5.31 μm, 5.22 μm, 5.16 μm or 5.07 μm; c. The D50 of the modified graphite material is 10-12 μm, for example, 11.51 μm, 11.38 μm, 11.21 μm or 11.19 μm; d. The D90 of the modified graphite material is 31-33 μm, for example, 32.10 μm, 31.46 μm, 31.13 μm or 31.01 μm; e. The specific surface area of ​​the modified graphite material is 1.5-2.5m 2 / g, for example 2.04m 2 / g, 1.98m 2 / g, 1.89m 2 / g or 1.87m 2 / g.

3. A method for preparing a modified graphite material, characterized in that: It includes the following steps: S1. Stirring a mixture containing aluminum salt, liquid asphalt and solvent to obtain a composite coating agent; the mass ratio of the aluminum salt to the liquid asphalt is (3-7):(5-15); the solubility of the aluminum salt at 25° C. is greater than 50 g / 100 mL; S2, mixing the composite coating agent and the graphite material in step S1 uniformly to obtain a graphite material coated with the composite coating agent; S3. The graphite material coated with the composite coating agent is subjected to heat treatment and carbonization to obtain a modified graphite material; the heat treatment temperature is 350-500°C.

4. The method for preparing the modified graphite material according to claim 3, characterized in that: Step S1 satisfies one or more of the following conditions af: a. The mass ratio of the aluminum salt to the liquid asphalt is 6:10, 5:10, 4:10 or 3:10; b. The aluminum salt is anhydrous aluminum nitrate and / or aluminum nitrate nonahydrate, such as aluminum nitrate nonahydrate; c. The solvent is deionized water and / or ethanol; preferably, the solvent is deionized water and ethanol, and the volume ratio of the deionized water to the ethanol is (1-10):1, for example 1:1, 1.5:1, 2.33:1 or 4:1; d. The mass ratio of the aluminum salt to the solvent is (0.2-0.8):1, for example 0.6:1, 0.5:1, 0.4:1 or 0.3:1; e. The stirring time is 10 to 20 min, for example 10 min; f. The solubility of the aluminum salt at 25°C is 70g / 100mL.

5. The method for preparing the modified graphite material according to claim 3, characterized in that: The density of the liquid asphalt is 0.5-1.5 g / cm 3 , for example 1.10 g / cm 3 ; and / or, the sulfur content of the liquid phase asphalt is less than 0.15wt%, for example 0.10wt%; and / or, the ash content of the liquid phase asphalt is less than 0.03 wt %, for example 0.01 wt %; and / or, the coking value of the liquid phase asphalt is 5-20wt%, such as 5wt%, 10wt%, 15wt% or 20wt%; And / or, the composite coating agent has a carbon residue of 0.5wt%-2.0wt%, such as 0.5wt%, 1wt%, 1.5wt% or 2wt%.

6. The method for preparing the modified graphite material according to claim 3, characterized in that: Step S2 satisfies one or more of the following conditions ad: a. The graphite material is artificial graphite and / or natural graphite, for example artificial graphite b. The mass ratio of the composite coating agent to the graphite material is (1-3): 10, for example 1.6:10, 1.5:10, 1.4:10 or 1.3:10; c. Step S2 wherein the mixing is performed in a fusion machine; the mixing speed is preferably 400 to 900 rad / min, for example 900 rad / min; d. The mixing time is 5 to 15 minutes, for example 10 minutes.

7. The method for preparing the modified graphite material according to claim 3, characterized in that: Step S3 satisfies one or more of the following conditions af: a. The heat treatment adopts a segmented heating method, which comprises the following steps: ① Heating to 250-400°C, such as 400°C, 350°C, 300°C or 250°C; preferably, the heating rate is 1-5°C / min, such as 1.5°C / min; preferably, the constant temperature time of heating is 2-5h, such as 4h, 3.5h, 3h or 2.5h; ② Continue heating to 400-600°C, such as 600°C, 550°C, 500°C or 450°C; preferably, the heating rate is 1-5°C / min, such as 1.5°C / min; preferably, the constant temperature time of heating is 5-10h, such as 7h, 6.5h, 6h or 5.5h; b. The carbonization temperature is 950-1350°C, for example 1300°C, 850°C, 1000°C or 1150°C c. The carbonization time is 4-10h, for example 5h; d. The carbonization step further includes a screening step; the particle size range of the screening is preferably 100-400 mesh, such as 300 mesh.

8. A modified graphite material, characterized in that: The modified graphite material is prepared by the method for preparing the modified graphite material according to any one of claims 3 to 7.

9. Use of the modified graphite material as claimed in any one of claims 1, 2 and 8 as a negative electrode material in a lithium ion battery.

10. A lithium ion battery, characterized in that: It comprises the modified graphite material as claimed in any one of claims 1, 2 and 8.

Citation Information

Patent Citations

  • Netted gamma-aluminum oxide coated modified graphite negative electrode material as well as preparation method and application thereof

    CN113363445A

  • Coated Si-base composite material

    CN102983314A

  • Coated graphite lithium ion battery negative electrode material and preparation method thereof

    CN108305994A

  • Low-crystallization-degree coating material and preparation method thereof, anode material and lithium battery anode

    CN111785915A

  • Coating agent, fast-charging graphite, preparation method and application of fast-charging graphite and battery

    CN112803001A